Active Motor Training Has Long-term Effects on Infants’ Object Exploration - Wiesen, Sarah E.; Watkins, Rachel M.; Needham, Amy Work (Frontiers in Psychology, 2016)
Long-term changes in infants’ behavior as a result of active motor training were studied. Thirty-two infants completed three visits to the laboratory. At the first visit, infants were three months old and completed an object exploration assessment. Then the experimenter demonstrated the motor training procedures appropriate for the infant’s experimental condition, and parents took home custom infant mittens (either sticky or non-sticky) and a bag of lightweight toys to practice with their infants. Over the course of the following two weeks, infants participated in ten sessions of either active (sticky) or passive (non-sticky) mittens training at home with their parents. Infants who participated in active mittens training wore mittens with the palms covered in Velcro, allowing them to pick up and move around small toys. Infants who participated in passive mittens training wore non-sticky mittens, and their parents moved the toys through their visual fields on their behalf. After completing the training, infants returned to the lab for the second visit. At visit two, infants participated in another object exploration assessment as well as a reaching assessment. Parents returned the training materials to the lab at the second visit, and were told not to continue any specific training regimen from this point forward. Two months later, when infants were about five and a half months of age, they returned to the lab for a third visit. At the third visit, infants completed the same two assessments as during the second visit. The results of this study indicate that infants who participated in active motor training engaged in more sophisticated object exploration when compared to infants who received passive training. These findings are consistent with others in the literature showing that active motor training at 3 months of age facilitates the processes of object exploration and engagement. The current results and others reveal that the effects of early experience can last long after training ceases.